Community analysis of nematodes associated with Philodendron burle-marxii with a new record of Meloidogyne incognita in Thiruvananthapuram, Kerala, India - Narayana, R.; Pooja , V. (ENTOMON, 2026)
Survey conducted on Philodendron burle-marxii, an ornamental plant, in 13 panchayats of Thiruvananthapuram district, Kerala, revealed the occurrence of plant parasitic nematodes like Meloidogyne incognita, Rotylenchulus reniformis and Helicotylenchus dihystera; and predatory nematodes such as Iotonchus indicus and Mylonchulus minor. Rhabditids and other free-living nematodes were also encountered. The highest population of M. incognita was recorded from Vallakadavu area of Thiruvananthapuram Corporation (199 J2 200 cm3 soil-1) followed by Veniyoor area of Venganoor panchayat. The highest population of R. reniformis was recorded from Pallichal area of Kalliyoor panchayat (99 nematodes 200 cm3 soil-1). The highest population of I. indicus was from Ponmudi area of Peringamala panchayat (3.5 nematodes 200 cm3 soil-1) and that of M. minor was from Peppara area of Vithura panchayat (6 nematodes cm3 soil-1). The bacterial feeding nematodes belonging to order Rhabditida was recorded from all the areas sampled. M. incognita recorded the highest prominence value to a tune of 1827.0 and 2959.0 for both Nemom and Vamanapuram respectively. This is the first report of M. incognita infecting P. burle-marxii in India evidenced by the morphology of female and second stage juveniles. The infected plants exhibited stunting, chlorosis of the lower leaves, abnormal leaf glossiness, and crinkling, curling, and a reduction in leaf size ranging from 30 to 80 per cent.